Earth Gravity Detection System with Altitude Variations Using Phypox Application Integrated with Smartphone Acoustic Sensors - Sebastian, Rio; Suparno, Suparno; Winingsih, Puji Hariati; Saputro, Handoyo; Hapsari, Nadya Amalia Putri (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2023)
This study aims to examine the effect of altitude on the acceleration of gravity with the help of smartphone acoustic sensors. The altitude varies from the interval 100-1061 MASL (Mean Above Sea Level), located around the Special Region of Yogyakarta. An iron ball is dropped from a certain height, and the time it falls is observed using an acoustic sensor in Phypox, and the results are used to determine the acceleration value due to gravity (g) through the equation g = 2h/t2. Fitting data from measurements of the four altitude variations are shown in the polynomial equation y = 0.000003x2 – 0.0035x +10.718 m/s2 with a regression number R2 = 1,000. This equation shows that the acceleration value due to gravity will decrease quadratically with each increase in the altitude per meter above sea level.